Greek FDI in the Balkans: How is it affected by the crisis in Greece? - Persephone Economou; Margo Thomas (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Greece accounts for only 6% of the Balkan countries' combined inward FDI stock, but Greek banking presence in the Balkans is significant. The sovereign debt crisis and recession in Greece are having a negative effect on Greek FDI into the Balkans, but it is the reduced lending by Greek bank foreign affiliates or their possible withdrawal that will have a bigger impact on the local economies.
Keywords: 330